Application of low-intensity ultrasound as a rapid, cost-effective tool to wheat screening: A systematic frequency selection. (July 2018) - Salimi Khorshidi, Ali; Thandapilly, Sijo Joseph; Ames, Nancy
Abstract: A preliminary study on the potential of low-intensity ultrasound for wheat screening purposes was carried out. A transmission technique with the use of longitudinal ultrasonic waves at five frequencies was utilised (0.5–10 MHz) to enable selection of the frequency at which the best discrimination and quality evaluation of five Canadian wheat varieties are achieved. Mixograph, farinograph and micro-extension parameters were also determined for comparison purposes. Statistical interpretation of the data was performed using principal component analysis (PCA) and generalized linear model (GLM). Results indicated that ultrasonic measurements at 10 MHz allowed for better discrimination of wheat varieties with a reasonable degree of confidence, compared to other frequencies. Moreover, correlations between parameters derived from ultrasonic measurements at 10 MHz and those of mixograph, farinograph and micro-extension were found to be significant (P ≤ 0.05) and in good agreement with the definitions of the parameters studied. Based on the statistical analysis of the data, ultrasonic phase velocity and longitudinal storage modulus at 10 MHz were found to be the best discriminators of the wheat varieties used in this study. Highlights: Rapid and cost-effective evaluation of wheat flour dough rheology using ultrasound. High sensitivity of ultrasound wave (1–10 MHz) to differences among wheat varieties. Best wheat variety discrimination power of low-intensity ultrasound at 10 MHz. Agreement between ultrasound and conventional tests in evaluating dough strength. Great potential of low-intensity ultrasound at 10 MHz for wheat screening.